Pengaruh Tingkat Pendapatan, Suku Bunga, Religiusitas, dan Financial Attitude terhadap Minat Menabung untuk Beryadnya pada Masyarakat Desa Tajun - Kd. Doni Swastawan; Ni Wyn. Yulianita Dewi (Universitas Pendidikan Ganesha, 2021)
This study aimed to determine the effect of income levels, interest rates, religiosity, and financial attitudes towards saving interest for Yadnya in Tajun Village community. The population was 388 people with a selected sample of 93 people. The type of research used was quantitative research with a descriptive design. Data were collected through a questionnaire. The collected data was tested first with validity and reliability tests. Furthermore, the data were analyzed using descriptive statistical test, classical assumption test and hypothesis test. This study showed that 1) the income level had a partial effect on the interest in saving for the sake of the people of Tajun Village, 2) the interest rate had a partial effect on the interest in saving for the sake of the people in the Tajun Village, 3) religiosity had a partial effect on the interest in saving for the sake of the people in the Tajun Village. Tajun, 4) Financial Attitude partially affects the interest in saving for the sake of the people of Tajun Village, 5) Income Level, Interest Rate, Religiosity, and Financial Attitude simultaneously affect the interest in saving for the sake of the people tajun village.